How does leaders' information-sharing behavior affect subordinates' taking charge behavior in public sector? A moderated mediation effect - Liu, Jun-Na; Hou, Yun-Zhang; Wang, Jun; Fu, Ping; Xia, Cong-Zhen (Frontiers in Psychology, 2022)
Taking charge behavior of civil servants is an important part of individual innovation performance, which is not only a key step of innovation in the public but also a real need for high-quality cadres’ construction in the public sector in the new era. Therefore, it is necessary to carry out an in-depth discussion on civil servants' taking charge behavior. Based on the theory of planned behavior, this paper constructs the framework of "cognition-motivation-behavior" to deeply explore the relationship between public sector leaders' information-sharing behavior and subordinates' taking charge behavior, as well as the mediating and moderating effects of subordinates' public service motivation and emotional trust. Taking 200 civil servants’ questionnaire surveys as samples, the empirical study finds that the information-sharing behavior of leaders in the public sector can significantly affect taking charge behavior of subordinates; the public service motivation partially mediates the relationship between them; emotional trust positively moderates the mediation effect of public service motivation in the relationship between leaders' information sharing behavior and subordinates' taking charge behavior in the public. This study not only enriches the research on civil servants' taking charge behavior theoretically but also provides meaningful enlightenment for promoting civil servants’ taking charge behavior.